2016
DOI: 10.1182/blood-2016-02-697003
|View full text |Cite
|
Sign up to set email alerts
|

miR-125b controls monocyte adaptation to inflammation through mitochondrial metabolism and dynamics

Abstract: Key Points• miR-125b reduces mitochondrial respiration and promotes elongation of mitochondrial network through BIK and MTP18 silencing, respectively. • The miR-125b/BIK/MTP18 axis promotes adaptation of monocytes to inflammation.Metabolic changes drive monocyte differentiation and fate. Although abnormal mitochondria metabolism and innate immune responses participate in the pathogenesis of many inflammatory disorders, molecular events regulating mitochondrial activity to control life and death in monocytes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 69 publications
2
65
0
Order By: Relevance
“…Up‐regulation of miR‐125b expression maintained the body weight and survival of ALI mice and significantly reduced LPS‐induced pulmonary inflammation . Another study showed that increased miR‐125b through toll‐like receptor 4(TLR4) affected mitochondrial respiration and dynamics through BIK and MTP18 silencing, respectively, promoting pro‐inflammatory activation and apoptosis of monocytes . Nrf2 has attracted increased attention as a protective transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…Up‐regulation of miR‐125b expression maintained the body weight and survival of ALI mice and significantly reduced LPS‐induced pulmonary inflammation . Another study showed that increased miR‐125b through toll‐like receptor 4(TLR4) affected mitochondrial respiration and dynamics through BIK and MTP18 silencing, respectively, promoting pro‐inflammatory activation and apoptosis of monocytes . Nrf2 has attracted increased attention as a protective transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which miRNAs are regulated and expressed under normal or disease conditions are currently of great interest. Although miR-125b has been implicated in various cancers [12, 25-27], and might contribute to persistent inflammation [28, 29], this is the first indication about the role of miR-125b in chondrocytes inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…At this time we know, for example, that human monocyte derived inflammatory macrophage produce TNF, IL-1β and IL-6, and exhibit broadly similar metabolic characteristics including increased glycolytic activity, diminished OXPHOS, the production of itaconate, increased oxidative stress, and the depletion of intracellular NADPH and NAD+ after LPS stimulation. 30,41,114 However, human monocyte-derived macrophages do not express NOS2 or make NO after LPS stimulation, [115][116][117][118][119] and therefore will not experience the pseudo-hypoxic conditions that inflammatory mouse macrophages are subjected to. Moreover, the subtleties of NAD+ synthesis may also differ between inflammatory macrophages from the two species.…”
Section: Future Pros Pec Tsmentioning
confidence: 99%